Harmonization of laws regulating the formation of village government work plan drafting teams - Dharma, Bagus Surya; Prasetio, Dicky Eko; Masnun, Muh. Ali; Lestari, Putri Diah (Ex Aequo Et Bono Journal Of Law, 2025)
Background: This research aims to analyse the arrangements related to the formation of the Village RKP Compilation Team as stipulated in Permendagri 114/2014 and Permendesa PDTT 21/2020 and to analyse legal harmonisation efforts related to conflicts between Permendagri 114/2014 and Permendesa PDTT 21/2020. Methods: This research is a normative legal research that prioritises conceptual and statutory approaches. Findings: The results confirm that the authority to form the Village RKP Compilation Team has moved to the Ministry of Villages, Development of Disadvantaged Regions and Transmigration so that regulations from the ministry are prioritised for use. Conclusion: The resolution of norm conflicts between Permendagri 114/2014 and Permendesa PDTT 21/2020 regarding the formation of the Village RKP Compilation Team can be done by harmonising regulations using the principle of preference, specifically the principle of lex superior derogate legi inferiori in harmonising authority in village development and the principle of lex posterior derogate legi priori in harmonising regulations on the formation of the Village RKP Compilation Team. Novelty/Originality of this article: Through harmonisation using the principle of preference, the regulation on the formation of the Village RKP Compilation Team regulated by Permendesa PDTT 21/2020 takes precedence over its use.